Glycemic impact of a diet and lifestyle intervention on diabetics and prediabetics during treatment for non-muscle invasive bladder cancer. (2nd October 2020) - Chestnut, Connor; Smelser, Woodson; Dum, Travis; Bechtel, Misty; Hand, Lauren; Michel, Carrie; Bawajeeh, Areej; Zohreh, Sepideh; Liu, Weiya; Anant, Shrikant; Robbins, David; Holzbeierlein, Jeffrey M.; et al.
Abstract: Introduction: Patients with Type II Diabetes Mellitus (DM2) have increased risk of recurrence and progression of non-muscle invasive bladder cancer (NMIBC). Glucose control through lifestyle intervention is an uninvestigated, attractive strategy to decrease risk of cancer recurrence. We test the feasibility of a diet and exercise program and its glycemic impact in patients with DM2 and NMIBC. Materials/methods: Five participants with NMIBC and pre-diabetes or DM2 were recruited for a pilot, prospective clinical trial. Each participant received dietary counseling for 16 sessions during clinical visits. The intervention included a carbohydrate-restricted (CR) diet (<130 grams per day), 30 min, walking 5×/wk, and 5000 steps daily. Diet compliance was measured with 24-hour diet recall. Exercise was monitored with accelerometer and self-report. Results: Five participants enrolled and two participants completed the 12-month intervention. Adherence was 60% to CR diet and 84% to exercise goals. Participants reduced carbohydrate consumption by 44%. Participants showed reductions in fasting blood glucose, HbA1c, glucosuria, fasting blood insulin, and body weight, and increased euglycemia on continuous glucose monitoring. Conclusions: Adherence to a CR diet and exercise goals is feasible in patients with NMIBC and DM2 and also leads improved glucose control. A phase-II trial on bladder cancer-specific outcomes is warranted.